แนวทางการพัฒนาภาวะผู้นำแบบกระจายความเป็นผู้นำของผู้บริหารโรงเรียนสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษา - ปาจรีรัตน์ อิงคะวะระ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This study is a descriptive research with the purposes to 1) study the current and desirable conditions of Distributed Leadership of school administrators under the primary education service area. 2) provide approach for Distributed Leadership of school administrators under the primary education service area. The informants of this research were 234 people: school director and teacher from 78 schools under the Suphanburi primary educational service area office 1. The research instrument utilized were rating-scale questionnaire and applicability and possibility evaluations of guidelines for Distributed Leadership of school administrators under the primary education service area in which the implemented statistic features were frequency distribution, percentage, mean, standard deviation. The collected data were analyzed to compute and arrange priority by Modified Priority Index Formular. ((PNImodified)) From the results of this research, it was found that 1) overall current and desirable conditions of Distributed Leadership of school administrators under the primary education service area were at a High Level and Highest Level respectively; the top priority were Share vision, mission, and goals (PNImodified =0.213); followed by Decision making (PNImodified = 0.207); Collaboration and cooperation (PNImodified =0.206); and Responsibility and accountability (PNImodified =0.178) respectively. There were 4 main approaches and 12 guidelines including 3 guidelines of Developmental relationships for Share vision, mission, and goals; 3 guidelines of Developmental relationships for Decision Making; 3 guidelines of Developmental relationships for Collaboration and cooperation; 3 guidelines of Executive coaching for Responsibility and accountability.